Superior thermally robust energetic materials featuring Z–E isomeric bis(3, 4-diamino-1, 2, 4-triazol-5-yl)-1H-pyrazole: self-assembly nitrogen-rich tubes and templates with Hofmeister anion capture architecture. Issue 18 (22nd April 2020) - Geng, Wenjing; Jia, Yunfei; Chen, Ya; Ma, Qing; Fan, Guijuan; Liao, Longyu
Abstract : A super thermally robust nitrogen-rich framework was synthesized, and Z → E isomerization as well as supramolecular assembly inclusion strategy gave rise to two different nitrogen-rich tubes and templates with Hofmeister anions capture architecture. Abstract : A novel nitrogen-rich energetic material, namely 3, 5-bis(3, 4-diamino-1, 2, 4-triazole)-1 H -pyrazole, was synthesized via a one-step reaction from commercially available reagents and its single-crystal X-ray analysis revealed that the conformational isomerism of this new energetic material was associated with the configuration of pyrazole ( trans or cis ) as a cation in the presence of two Hofmeister anions. Their structures were fully determined via 1 H, 13 C NMR, and infrared spectroscopies as well as elementary analysis. Single-crystal X-ray diffraction was employed for characterizing their crystal structures. It is worth noting that the detonation velocity and sensitivity ( D : 9275 m s −1, IS > 40 J, FS = 360 N) of 3, 5-bis(3, 4-diamino-1, 2, 4-triazole)-1 H -pyrazole (EM3 ) are superior to those of RDX. Meanwhile, 3, 5-bis(3, 4-diamino-1, 2, 4-triazole)-1 H -pyrazole and its supramolecular assembly energetic materials (EM3 –EM5 ) exhibit great thermal stability ( T d : 280–358 °C), suggesting that they are also heat-resistant energetic materials. The above-mentioned energetic performances show that they are insensitive and have further potential applications as metal-free detonating substances.